About a case of micropenis - G. Bolla; I. Mammi (PAGEPress Publications, 2013)
The early hormonotherapy of micropenis takes on a diagnostic significance too. The very good tolerance gives value to this behaviour. The Author shows the condition of a male infant 46,XY eighteen months old; the child appeared with a micropenis completely expressed and resulting from hypogonadotropic hypogonadism. He confirms the good response to hormonotherapy for this child.